Clinical Applications of Tumor Volume Measurements for Predicting Outcome in Patients with Squamous Cell Carcinoma of the Upper Aerodigestive Tract - Mukherji, Suresh K.; Schmalfuss, Ilona M.; Castelijns, Jonas; Mancuso, Anthony A. (American Journal of Neuroradiology, 2004)
Gross tumor volume (GTV) at the primary site, as derived from pretreatment CT findings, can help predict local control of squamous cell carcinoma at different head and neck subsites after treatment with nonsurgical organ preservation. Local recurrence is more likely with large tumors than with small lesions in the same anatomic subsite, and GTV is often more strongly associated with local control than is tumor stage. This review discusses tumor volume calculation—technique, current literature, and potential clinical applications—and aims to help the reader to understand the role of GTV calculations and to integrate this knowledge into clinical practice.